Effect of Endomorphins on HUVECs Treated by ox-LDL and Its Related Mechanisms - Juan Zhao; Qi Zhang; Jing Liu; Liming Tian; Wenhui Huang; Jinxing Quan; Jinyang Wang; Yanjia Xu; Yunfang Wang; Ruilan Niu (Journal of Diabetes Research)
We found in the present study that treatment with ox-LDL decreased the cell viability and the content of nitric oxide (NO) and the activity of nitric oxide synthase (NOS) as well as eNOS mRNA expression, while increasing the mRNA expression and content of endothelin-1 (ET-1) in human umbilical vein endothelial cells (HUVECs). However, endomorphins EM1/EM2 increased the cell viability and the content of NO and the activity of NOS as well as eNOS mRNA expression, while decreasing the mRNA expression and content of ET-1 compared with ox-LDL alone. Meanwhile, the expressions of JNK and p-JNK were enhanced by ox-LDL while being suppressed by EM1/EM2. The results suggested that EM1 and EM2 can correct the endothelial cell dysfunction induced by ox-LDL and the protective effect may be achieved by affecting the JNK pathway.